Quality in drug administration by enteral catheters from an intensive care unit in Mexico - Méndez-Jiménez, Ana Gabriela (2017)
This work has like main purpose evaluate the quality in drug administration by enteral probes in nurses by an Intensive Care Unit. Methodology: observational, transversal and descriptive study. Considered the total number of nurses (N = 30) a high specialty Hospital. We studied the variables knowledge and compliance. To assess knowledge in the ministration of drugs for probes enteral was used the instrument of Amuriza "Survey of administration of drugs". To assess compliance in the administration of oral medications, used oral drug administration official card of national system of indicators of quality in health. To obtain the quality level, it created a weighted General index (IPG) from the sum of the estimated values retrieved from the percentage and the average of the level of knowledge and level of compliance score. The data were analyzed through the statistical program SPSS v.21.0). Results: Average knowledge level was deficient in the participants, the level of compliance was intermediate in 77%, weighted quality level was 5-point estimated as deficient. Conclusions: The result is contrary to established guidelines for administering drugs by probes, training and constant evaluation for continuous improvement is suggested. It is essential for good to know and do well in nursing interventions